Perspective article: Challenges Toward Developing African Swine Fever Virus Vaccine (Global Journal of Medical Research, 2023)
African swine fever virus is one of the most common viruses that infect swine population This virus causes a systemic disease to swine named African swine fever The virus was first identified in Africa in 1921 Montgomary 1921 African swine fever virus is a member of the Asfarviridae family and it is the only DNA virus within that family Costard et al 2013 Though the virus is endemic to Africa the virus has been reported to infect swine population in European countries as well most prominently in the Caucasus region and Russian Federation African swine fever virus is highly contagious and can lead to 100 morbidity Costard et al 2013 The mortality rate due to the disease is varying The transmission cycle of the virus can continue with or without the presence of the vector NAHIS The usual vector in the transmission cycle is the soft ticks of the Ornithodoros species Guinat et al 2016 The natural host of the virus is domesticated pigs wild boar bush pigs warthogs and giant forest hogs Vector-mediated transmission occurs through the bites of Ornithodoros spp soft ticks These are bloodsucking ticks that can transmit the infectious agent from one host to another